2004
DOI: 10.1542/peds.2004-1409
|View full text |Cite
|
Sign up to set email alerts
|

Providing a Primary Care Medical Home for Children and Youth With Cerebral Palsy

Abstract: ABSTRACT. Children and youth with cerebral palsy present pediatricians with complex diagnostic and therapeutic challenges. In most instances, care also requires communication and comanagement with pediatric subspecialists and pediatric surgical specialists, therapists, and community developmental and educational teams. The importance of family resilience to the patient's wellbeing broadens the ecologic scope of care, which highlights the value of a primary care medical home from which care is initiated, coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 60 publications
4
41
0
1
Order By: Relevance
“…Moderate and severe HIE were significant risk factors of CP, as were grade 3 and 4 IVH. Ultrasound abnormalities associated with CP included PVL, grade 3 and 4 IVH, encephalomalacia, meningitis, hydrocephalus, and ventriculomegaly, which were similar to previous findings in the published literature.1 [3][4][5][6][7][8][9][10][11][12][13][14][15] The diagnosis of CP is straightforward in cases of severe CP or in older children. It is difficult to accurately diagnose CP in the first 6 months of life, in milder cases, or in cases of isolated motor delay.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Moderate and severe HIE were significant risk factors of CP, as were grade 3 and 4 IVH. Ultrasound abnormalities associated with CP included PVL, grade 3 and 4 IVH, encephalomalacia, meningitis, hydrocephalus, and ventriculomegaly, which were similar to previous findings in the published literature.1 [3][4][5][6][7][8][9][10][11][12][13][14][15] The diagnosis of CP is straightforward in cases of severe CP or in older children. It is difficult to accurately diagnose CP in the first 6 months of life, in milder cases, or in cases of isolated motor delay.…”
Section: Discussionsupporting
confidence: 70%
“…3 Early detection of CP within the first year of life is essential to enable early intervention, which will affect the natural course of the disease. 4 Identification of CP in young infants is problematic due to the limited motor development in these infants, making it difficult to determine the types of motor delay that can be used to detect CP.…”
mentioning
confidence: 99%
“…This could occur because several studies have shown associations between low income and poor oral health. Families from low SES group lack of knowledge which led to poor home care management skills 6 . The SES is considered one factor which affects mothers' nurtures of the children care.…”
Section: Resultsmentioning
confidence: 99%
“…22 Other stated that the brain injury resulting in cerebral palsy may also affect higher cognitive functioning, resulting in evidence of learning disability, language and communication impairment. 6 Most mothers were in child bearing age. The disabilities were mainly due to financial problems rather than inadequate preparation to care for the child or lack of information regarding the condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation